Analysis of preference Consumers Against Coffee Local at Regency Muna - Sawalludin, Sawalludin; Rianda, La; Baco, Abdu Rahman (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2020)
The study aims to determine factors that influence the preference of consumers to coffee locally in Regency Muna, to determine the priority choice of consumers to coffee locally in Regency Muna, and to determine a shift in the balance of consumers to coffee Local in Regency Muna.The population in this study are consumers who buy and consume coffee at the study site, the determination of the sample is done by random sampling to obtain 75 respondents. Data collection is done through interviews, questionnaires, and documentation. Data analysis using multivariate regression analysis with the help of SPSS 16 for windows, analysis of exponential comparison methods and markov analysis. The results of this study indicate that consumer preferences for local coffee on taste variables have a significant effect with a significant value of n 0,000 <0.05, aroma variables have a significant effect 0,000 <0.05, and color variables have a significant effect 0,000 <0.05, MPE analysis shows that local kahawai coffee still has a great opportunity as a priority for consumers in the consumption of coffee in the Maabholu Village, and Markov analysis shows the equilibrium point in the 16th period namely local kahawai coffee 0.243, instant ABC Mocca coffee 0.387, instant coffee boat fire 0.230, and instant coffee Tora Bika 0.054.